Prognostic implications of unrecognized myocardial infarction before elective percutaneous coronary intervention. (3rd October 2022) - Nogami, K; Hoshino, M; Kanaji, Y; Sugiyama, T; Misawa, T; Hada, M; Yamaguchi, M; Nagamine, T; Teng, Y; Ueno, H; Matsuda, K; Sayama, K; et al.
Abstract: Background: A non-negligible proportion of myocardial infarction (MI) is not clinically recognized and unrecognized myocardial infarction (UMI) is associated with adverse outcomes. Purpose: To determine the prevalence and prognostic significance of UMI by delayed-enhancement cardiac magnetic resonance (DE-CMR) before elective percutaneous coronary intervention (PCI). Methods: In this prospective, single-center study, 236 patients with stable coronary artery disease undergoing elective and uncomplicated PCI were studied. All patients underwent DE-CMR before PCI. The prevalence of UMI was evaluated and the association of clinical and CMR-derived variables with primary MACE, defined as cardiovascular death, nonfatal MI, hospitalization for heart failure, unplanned late revascularization, and ischemic stroke was investigated. Results: In the final analysis of 213 patients, 63 patients (29.6%) showed UMI. Target territory UMI was observed in 38 (17.8% of total, 60.3% of patients with UMI). UMI was significantly associated with sex, diabetes mellitus, left ventricular ejection fraction, SYNTAX score and fractional flow reserve in target vessels. During follow-up periods (median, 23 months), MACE was observed in 17 (27.0%) of patients with UMI, and 17 (11.3%) without (P=0.001). In a multivariable model, UMI (hazard ratio [HR] 2.18, 95% confidential interval, 1.10–4.33, P=0.001) remained as an independent predictor of MACE. Kaplan–Meier analysis indicated that the presence of UMI was significantly associated with higher incidence of MACE. Conclusions: The prevalence of UMI in patients undergoing elective PCI was 29.6%. UMI was independently associated with an increased risk of MACE after successful PCI. Given the non-negligible prevalence and potential clinical significance of UMI, clinical studies comparing PCI and guideline directed medical therapy (GDMT) versus GDMT only strategy might have to take the presence of UMI into consideration. Funding Acknowledgement: Type of funding sources: None.